Filiform Fire Needling Combined with Electroacupuncture in Treating 30 Cases of Obstinate Peripheral Facial Paralysis - Minqin ZHENG; Zhenwei CHEN (康复学报)
Objective:To observe the therapeutic effect of filiform fire needling combined with electroacupuncture in obstinate peripheral facial paralysis (OPFP).Methods:Sixty OPFP patients were assigned into the treatment group and the control group by a random number table, and 30 patients were in each group. The control group received electroacupuncture, once a day. The treatment group received filiform fire needling every other day, combined with electroacupuncture once a day. A treating course consisted of ten days of treatment, and the complete treatment lasted for four courses. The classification of House-Brackmann and Portmann scores were used to evaluate the therapeutic effect of two groups.Results:The Portmann scores were increased after treatment in both groups (P<0.01, P<0.05), more increase in treatment group than that in control group (P<0.05). After the treatment, there were significant differences in the classification of House-Brackmann and Portmann scores between the two groups. The therapeutic effect of treatment group was better than that of control group (P<0.05). No significant difference showed in the safety and pain tolerance between the two groups.Conclusion:The therapeutic effect of filiform fire needling combined with electroacupuncture is better than that of single electroacupuncture therapy.